El discurs eclesiàstic davant el món visionari femení en els segles XVI i XVII. - ALABRÚS, ROSA MARIA (Scripta, 2016)
The article describes the evolution of ecclesiastical discourse about female religiosity from the irst manifestations of Illuminism. It stands the signiicance of the work of Teresa of Jesus in the construction of the female visionary world. Attitudes on the question of Archdeacon Juan de Horozco, the Franciscan Gerónimo Planes and the Discalced Carmelite Maties de Sant Antoni Carbó are exposed. It demonstrated the effort by combining the legitimacy of the visions of Teresa with progressive ecclesiastical misgivings about the female imagination.